Pengaruh Kepemimpinan Transformasional Dan Manajemen Konflik Terhadap Komitmen Organisasi Perum Lembaga Penyelenggara Pelayanan Navigasi Penerbangan Indonesia Kantor Cabang Pembantu Bengkulu - Muhammad Avicena; Dodi R Setiawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The purpose of this study was to study the effect of transformational leadership and conflict management on organizational commitment of Perum LPPNPI Bengkulu Sub-Branch Office. The method used to analyze this research is a casual study. The sample of this study was all the population who were registered as employees at the Bengkulu Sub- Branch Office as many as 70 people. From the results of this study it was found that: (1) there was a significant positive effect between the transformational leadership variables on the organizational commitment variable; (2) there is a significant positive effect between conflict management variables on organizational commitment variables; (3) there is a significant positive effect between the variables of transformational leadership and conflict management simultaneously on the variable of organizational commitment.According to these findings, it can be concluded that employees' organizational commitment is influenced by transformational leadership and conflict management. And conflict management has the most dominant effect on increasing organizational commitment. In other words, we can say that good transformational leadership and neat conflict management will increase individual organizational commitment of employees. Finally it is concluded that transformational leadership and conflict management should be considered in increasing the organizational commitment of official.